STRATEGI PENGEMBANGAN USAHATANI PERBENIHAN KENTANG DI KABUPATEN KERINCI - Kiloes, Adhitya Marendra; Puspitasari, Puspitasari; Syah, Muhamad Jawal Anwarudin; Udiarto, Bagus Kukuh (Program Studi Agribisnis Fakultas Pertanian Universitas Muhammadiyah Yogyakarta, 2019)
There are several problems of potato seed in the production center of Kerinci. The purpose of the study was to develop strategies for developing potato seed farming at the production center of Kerinci. The primary data gained from the Focussed Group Discussion (FGD) to formulate internal and external factors in the development of potato seed farming. FGD’s participants were expert respondents stakeholders in potato farming in Kerinci. The analysis technique uses SWOT analysis and Analytic Hierarchy Process (AHP). The results showed that there were four internal factors of strength such as of agroecological conditions, the existence of Potato Seedling Hall, the presence of breeders, and the development of processing industries. While three internal weaknesses were non-strategic locations, the dependent on seeds from outside the area, and limited seed supervisors. External factors of opportunity were preferred superior varieties, opportunities to be seed suppliers, and investment, as well as three threat external factors such as faked labeled seed, continuity of supply is not guaranteed, and the government is not paying enough attention to potato agribusiness. From these factors, eight alternative strategies were formulated. The results of AHP followed by sensitivity analysis indicate that the alternative policy that must be taken is strengthening the breeder to produce certified seeds and produce massively certified seeds at affordable prices.